Safety improvement on arm forces construction site - Rakidin, Faridah (2015)
There are many accidents on construction sites. This research is to study hazards on construction site and to propose methods to mitigate them. The research was carried out by reviewing journals and accident data from Department of Safety and Health (DOSH) and Social Security Organization (SOCSO). Questionnaires were formulated and distributed to 50 respondents which are safety and health officer, project manager, engineer and clerk of work. The answers from respondents were analysed using Cronbach’s Alpha for their reliability and Likert Scale, Hazard Identification, Risk Assessment and Risk Control (HIRARC) to determine the risk level. Relative Important Index (RII) was used to determine the complying and effectiveness of safety management programs. Based on the results it is found that using hand tools is the highest risk followed by repetitive work and hazardous housekeeping. To reduce the hazards on construction site it is proposed behaviour control, administrative control, engineering control and introduce PPE. The complying and effectiveness of safety management programs are only at level effective and comply